Novel methods for quantitative analysis and evaluation of effects of chronic exposure to microcystins by capillary electrophoresis and metabolomics studies - BIRUNGI, GRACE (My University, 2010)
This thesis describes capillary electrophoresis (CE) methods for separation and quantification of cyan toxins in water; and “metabolomics” and “metabonomic” approaches for investigation of the effect of exposure of a human cell line to low amounts of microcystins. Incidences of toxic algal blooms in water bodies have increased. Toxic algae releases toxins into water bodies which puts water consumers at risk of exposure. Exposure to algal toxins is associated with harmful effects such as hepatotoxicity. Humans are at risk of non-obvious exposure leading to chronic exposure to cyanobacterial toxins because contamination may not be visible to the naked eye. It is therefore important to develop analytical techniques which can adequately detect and quantify these toxins; moreover the effect of exposure to low amounts of microcystins in human has not been reported. Capillary zone electrophoresis (CZE), micellar electrokinetic capillary electrophoresis (MEKC) and microemulsion electrokinetic chromatography (MEEC) were developed to determine microcystins LA, LF, LR, LW, RR, YR, nodularin (related hepatotoxin) and cylindrospermopsin, a hepatotoxic alkaloid. The CE methods were validated for use on a portable capillary electrophoresis instrument. Solid phase extraction (SPE) enabled cleanup and pre-concentration of a real sample and detection limits after SPE of the real sample spiked with microcystins were 0.90 g/L (RR), 0.76 g/L (YR), and 1.10 g/L (LR), with relative standard deviation (% RSD) values of 9.9-11.7 % for peak area and 2.2-3.3 % for migration time respectively. SPE recoveries were 90.3 % (RR), 101.5 % (nodularin), 90.6 % (YR), and 88.2 % (LR). In MEEC, online pre-concentration with the aid of a solvent plug achieved a 2-10 fold increase in peak area and height and the detection limit was in the range of 0.15-3 µg/ mL. Freeze drying together with sample stacking was used to achieve detection limits of 0.2-1.1 g/L. These methods can be used for routine water analysis to monitor ix microcystins up to concentrations limits as set by the World Health Organisation (WHO) drinking water guidelines. In the investigation of microcystin toxicity, HepG2 cells were incubated in media spiked with microcystins LR, RR, YR or a mixture of the three microcystins at different concentrations. Then aliquots of the media were sampled at specific time intervals, extracted and analysed using one dimensional proton nuclear magnetic resonance (1H NMR) and direct injection mass spectrometry (DIMS). Data obtained was reduced by principal component analysis (PCA) using SIMCA P+ software. The use of PCA and “metabolic finger/foot printing” techniques, allowed a distinction between samples exposed to microcystins, those exposed to acetaminophen (positive control), and those that were not exposed (negative control samples). Components responsible for the differences in patterns observed on the PCA plots were profiled and several metabolites were identified. Generally exposure to microcystins in the range of 1 ng/mL to 100 ng/mL interfered with the metabolisms of carbohydrates, amino acids, organic acids and lipids. The effects were more severe as concentration increased and more prominent for microcystin LR compared to microcystins RR and YR. The “metabolomic/metabonomic” approach demonstrated usefulness in studying toxicity due to microcystin exposure.
Keywords: Quantitative analysis; metabolomic studies; Chronic exposure; capillary electrophoresis; Solid phase extraction